Phenotypic Stability for Fruit yield and its Components of Brinjal - Chaitanya, V.; Reddy, R. V. S. K. (International Journal of Bio-resource and Stress Management, 2022)
The present study was carried out at Vegetable Research Station, ARI, Rajendranagar, Hyderabad, Telangana State, India during kharif (June–October, 2014), rabi (October–February, 2014–15) and Summer (February–May 2015) to assess the performance of genotypes in terms of yield as well as quality across seasons under wide range of environments through phenotypic stability studies. Thirty brinjal genotypes were evaluated for yield and quality parameters under three environments comprising of three different seasons. The portioning of environments + (genotypes × environments) mean squares showed that environments (linear) differed significantly and were quite diverse with regards to their effect on the performance of the genotypes for fruit yield and quality traits. A perusal of stability parameters indicated two genotypes C3 and P6 showed stable performance for earliness, C3 for days to first fruit harvest and C3, C10, C16, C21, P1 fordays to last fruit harvest hence these genotypes were adapted to all types of environments. Among the stable hybrids, five hybrids C3, C11, C13, C16 and C21 were significantly more yield plant-1 and more number of marketable fruits plant -1 over the best check Chhaya. Whereas, for ascorbic acid content 5 hybrids i.e C2, C4, C11, C14 and C18 to be stable over the check Utkarsha. C3 was showed stable performance over best check Chhaya for the trait fruit and shoot borer infestation on shoots and four hybrids C3, C11, C13 and C21 were found to be stable for the trait fruit and shoot borer infetstation on fruits over the best check Chhaya.